Inter relação entre constituição e extinção de firmas no Brasil - Rocco, Leandro de Almeida (2008)
This study investigates a dynamic interrelationship between formation and extinction of firms in Brazil using a sample between January of 1985 and December of 2007, divided into two periods: 1985-1994 and 1995-2007. The findings of this analysis favor the formulation of policies to benefit the creation of news firms and to avoid companies to close down. This interrelationship is studied through a vector autoregressive model applied to panel data and a causality test. The results show that the formation of companies generates extinction in two different periods and extinction generates formation only in the post-Real Plan period.